2014
DOI: 10.1007/s40544-014-0064-0
|View full text |Cite
|
Sign up to set email alerts
|

Friction of low-dimensional nanomaterial systems

Abstract: When material dimensions are reduced to the nanoscale, exceptional physical mechanics properties can be obtained that differ significantly from the corresponding bulk materials. Here we review the physical mechanics of the friction of low-dimensional nanomaterials, including zero-dimensional nanoparticles, onedimensional multiwalled nanotubes and nanowires, and two-dimensional nanomaterials-such as graphene, hexagonal boron nitride (h-BN), and transition-metal dichalcogenides-as well as topological insulators.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 95 publications
1
28
0
Order By: Relevance
“…As illustrated in Figure a–d, three domains (SLG, BLG, and Cu) showing different friction responses in each panel can be clearly distinguished. Friction forces of both SLG and BLG domains are much smaller than that of bare copper substrate since an ideal graphene film is atomically smooth and has no dangling bond, resulting in low shear strength . Friction force of SLG is larger than that of BLG, which is consistent with previous literature .…”
Section: Resultssupporting
confidence: 90%
“…As illustrated in Figure a–d, three domains (SLG, BLG, and Cu) showing different friction responses in each panel can be clearly distinguished. Friction forces of both SLG and BLG domains are much smaller than that of bare copper substrate since an ideal graphene film is atomically smooth and has no dangling bond, resulting in low shear strength . Friction force of SLG is larger than that of BLG, which is consistent with previous literature .…”
Section: Resultssupporting
confidence: 90%
“…The combination of these actions allowed the GNS to stretch to a substantial extent during crack opening stage. Depending on its elasticity, an extensibility of 20% strain has been reported for graphene [42,43]. This analysis highlights the direct role of GNS towards arresting the crack progression and stress dissipation through crack-bridging toughening mechanism (Fig.…”
Section: Toughness and Reinforcement Mechanismmentioning
confidence: 68%
“…Some of the most recent work in this area is reviewed here and more thorough reviews, specifically on graphene, can be found elsewhere [52][53][54].…”
Section: Graphene: 2d or Not 2d? That Is The Questionmentioning
confidence: 99%